A LITERATURE REVIEW OF SOCIAL ENTREPRENEURSHIP: A SOLUTION FOR CHALLENGES IN THE GIG ECONOMY - Shalsabilla Shafira; Ritha F. Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The gig economy, a rapidly growing economic phenomenon, has transformed traditional employment paradigms and modern economic structures. It reflects a flexible labor market based on demand, occasional work, and typically task-based arrangements. However, the presence of the gig economy also poses various challenges for its workers, such as income uncertainty, a lack of social protection, job instability, and uncertain working hours. To address these challenges, social entrepreneurship emerges as a potential solution. With a creative and sustainable approach, social entrepreneurship can enhance the well-being and fairness of gig workers, as well as create a more equitable and inclusive work environment. This research explores the role of social entrepreneurship in addressing issues in the gig economy, with the hope of serving as a valuable source of information for gig workers, particularly in Indonesia.